A Bibliometric Review of Research on Gamification in Marketing: Reflections for Moving Forward - Rosli, Nadzirah; Omar Zaki, Hafizah (Universiti Utara Malaysia Press, 2023)
Gamification has become increasingly popular among businesses, institutions and consumers, especially since the emergence of Covid-19 pandemic. It has been widely used to promote positive changes in user behaviour, improve companies’ digital presence and provide immersive and engaging brand experiences. Though bibliometric studies on gamification have been conducted previously, information on citations and networking analysis emphasises marketing and consumer behaviour remains scarce. Thus, the purpose of this bibliometric study is to describe how gamification is structured and how it has evolved over time. To achieve this, we utilise citation analysis and co-word analysis to visually uncover the intellectual, conceptual and social network structures in gamification research. A total of 558 articles published between 2011 and 2021 were extracted from the Dimension.ai database through the PRISMA review process. The results reveal positive growth in gamification research between 2011 and 2021. The United States was the most productive and most cited country and the most productive and influential institution was Tampere University in Finland, which houses Juho Hamari, the most influential and most cited author. Additionally, the results reveal recent trends in gamification research including those related to value, brand and attitude as well as emerging trends including artificial intelligence. The results also reveal collaborations through co-authorship among authors, institutions and countries. Together, they depict the intellectual landscape of gamification as related to marketing and consumer behaviour. This is beneficial for both inexperienced and experienced scholars, practitioners, funding agencies and policymakers.